Simplified Life Cycle Analysis : A Rural School in La Pampa, Argentina - Marcilese, Mariela Inés (2014)
This study case is a rural school in La Pampa, Argentina, where we compare two energy efficiency systems for construction: the local traditional building type and a proposed one, based on passive system design during its life cycle. In addition, we assume savings of emissions of greenhouse-gases are valued in terms of Argentina´s energy matrix. The efficiency, in terms of energy, involves the consumption for its manufacture (extraction, transport and assembly of materials), construction, maintenance and dismantling, recycling and final disposal of waste. Knowing this information at the preliminary stage can be advantageous to evaluate the selected materials in terms of energy and cost savings to amortize its value over the life cycle, and introduce other types of design. At present, there are significant problems of resource scarcity. The implementation of the analysis of life cycle (LC) should be a significant contribution in the field of construction in reference to awareness about energy conservation and efficiency, and therefore contribute to the sustainable development of societies.